Effects of matrimonial Canon Law: pastoral aspects = Aspects pastoraux de l’activité du droit canonique matrimonial = Aspetti pastorali di diritto canonico nei confronti dell’istituzione matrimoniale - Přibyl, Stanislav (Philosophy & canon law, 2015)
The value changes in the Western world since the 1960s have been markedly strong as regards the youth towards marriage. This situation was reacted to already in the 1983 Code of Canon Law promulgated by Pope John Paul II. Canon law can thus more effectively become a relevant tool in the pastoral care for the betrothed and married spouses in the Catholic Church. However, the basis for such pastoral ministry is a thorough preparation of couples for marriage and their permanent spiritual accompaniment. Legal tools referred to in the present paper can contribute to solving unusual or difficult situations of the spouses and enabling them access to sacramental life.